Pathology of Epstein-Barr virus-related lymphomas in HIV (Hematology Meeting Reports, 2009)
Acquired immunodeficiency syndrome-related non-Hodgkin lymphomas (AIDS-NHL) represent a significant source of morbidity and mortality among HIV-infected individuals.1 According to body location and histologic criteria, the pathologic spectrum of AIDS-NHL includes systemic AIDS-NHL, primary central nervous system lymphoma (AIDS-PCNSL), plasmablastic lymphoma of the oral cavity (AIDS-PBL) and primary effusion lymphoma (AIDS-PEL).2 Systemic AIDS-NHL are histologically classified into AIDS-related Burkitt lymphoma (AIDS-BL) and AIDS-related diffuse large B-cell lymphoma (AIDS-DLBCL). All AIDS-PCNSL are histologically represented by DLBCL. Despite their clinico-pathologic heterogeneity, most AIDS-NHL derive from B-cells that have experienced the germinal center (GC) reaction3 and, therefore, have been exposed to the mechanism of somatic hypermutation (SHM) which normally targets the immunoglobulin variable region (IgV).